Mucosal immunization with lipopeptides derived from conserved regions of SARS-CoV-2 antigens induce robust cellular and cross-variant humoral immune responses in mice - Patel, Raj S.; Agrawal, Babita (Frontiers in Immunology, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent of COVID-19, has infected >600 million people in the ongoing global pandemic. Several variants of the SARS-CoV-2 have emerged in the last >2 years, challenging the continued efficacy of current COVID vaccines. Therefore, there is a crucial need to investigate a highly cross-protective vaccine effective against variants of SARS-CoV-2. In this study, we examined seven lipopeptides derived from highly conserved, immunodominant epitopes from the S, N, and M proteins of SARS-CoV-2, that are predicted to contain epitopes for clinically protective B cells, helper T cells (TH) and cytotoxic T cells (CTL). Intranasal immunization of mice with most of the lipopeptides led to significantly higher splenocyte proliferation and cytokine production, mucosal and systemic antibody responses, and induction of effector B and T lymphocytes in both lungs and spleen, compared to immunizations with the corresponding peptides without lipid. Immunizations with Spike-derived lipopeptides led to cross-reactive IgG, IgM and IgA responses against Alpha, Beta, Delta, and Omicron Spike proteins as well as neutralizing antibodies. These studies support their potential for development as components of a cross-protective SARS-CoV-2 vaccine.